La fidélité, cet éternel questionnement : critique de la morale de la traduction - Henry, Jacqueline (Meta, 1995)
AbstractSince the beginnings of translation, fidelity has generally been considered the goal to strive for, yet this concept has never been clearly defined. This article questions the validity of the term and its paradigmatic value. To this end, the author analyses how the notion has been used in translation studies, focuses on its moral and religious assumptions, and concludes by voicing the need for a new terminology.